Intra-operative Ultrasound as a Tool to Assess Free Borders of Primary Vascular Aortic Tumors During Resection. (2016) - Andersen, R.M.; Eldrup, N.
Abstract : Introduction: Primary vascular tumors are rare and, in general, have a poor prognosis. Complete resection is associated with a better prognosis. Radical resection depends on safe discrimination of tumor borders. Technical summary: A 54 year old woman presented with abdominal pain. Imaging revealed a mass in the thoracic aorta, highly suspicious of angiosarcoma which was confirmed post-operatively by histological analysis. Open surgery was performed. Prior to clamping of the aorta, intra-operative ultrasound established clear delineation of the tumor borders. Conclusion: Intra-operative ultrasound was, in this case, a safe and easy method to determine the tumor borders, providing a simple guide to in toto tumor removal.